QUALITY OF SERVICES AND FACILITIES ON INPATIENT SATISFACTION WITH STAFF COMPETENCE AS AN INTERVENING VARIABLE AT TAMAN KROCOK COMMUNITY HEALTH CENTER - Aprilia Windarti; Toni Herlambang; Abadi Sanosra (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
The study was conducted at the Taman Krocok Health Center, Bondowoso with the aim of testing and analyzing the effect of service quality and infrastructure on patient satisfaction mediated by the competence of officers. The objects of the study were residents who were registered as inpatients at the Taman Krocok Health Center. The number of respondents was 125 people. The results are service quality had a positive and significant effect on the competence of officers at the Taman Krocok Health Center. Facilities and infrastructure had a positive and significant effect on the competence of officers at the Taman Krocok Health Center. Service quality had a positive but not significant effect on the satisfaction of inpatients at the Taman Krocok Health Center. Facilities and infrastructure had a positive and significant effect on the satisfaction of inpatients at the Taman Krocok Health Center, Bondowoso. Competence has a positive and significant effect on inpatient satisfaction at Taman Krocok Health Center, Bondowoso. Service quality has a positive and significant effect on inpatient satisfaction through the competence of Taman Krocok Health Center officers, Bondowoso. Facilities and infrastructure have a positive and significant effect on inpatient satisfaction through the competence of Taman Krocok Health Center officers.